Carcinoma medular de tiroides familiar (CMTF): primera familia descripta con CMTF asociado a la mutación Cys611Trp del proto-oncogen RET* - Gianotti, Tomás Fernández; Fainstein Day, Patricia; Russo Picasso, María Fabiana; Knoblovits, Pablo; Figari, Marcelo (Revista del Hospital Italiano de Buenos Aires, 2004)
Multiple endocrine neoplasia type 2 (MEN 2) is an autosomal dominant syndrome identified to date in 500-1.000 kindreds. All variants of MEN 2 show a penetrance higher than 90% for medullary thyroid carcinoma (MTC), whilst the penetrance for pheochromocytoma (50%) and parathyroid tumors (25%) is lower and variable. Familial medullary thyroid carcinoma (FMTC) is a rare variant of MEN 2, in which four or more members of a family have MTC without pheochromocytoma or primary hyperpathyroidism. In recent years genetic testing for the proto-oncogene RET mutations in the index case of MTC and in possible carriers has been used, because it has been demonstrated that prophylactic thyroidectomy before 2 – 5 years of age can prevent or cure MTC in MEN 2, even before its biochemical expression. Prophylactic thyroidectomy is not so clearly beneficial in FMTC. Mutations in the proto-oncogene RET (10q11.2) affect codon 634 in 80 – 90%, and less frequently, codons 918 (10-20%), 620 (6-8%), 618 (3-5%), 611 (2-3%) and 609 (0-1%). In this report we describe a family with an infrequent mutation in the proto-oncogene RET, Cys611Trp, (only one case reported in the bibliography). This mutation had not been detected in a previous genetic study, and we discuss herein the clinical management. Two approaches for the 2 asymptomatic young carriers: 1) prophylactic thyroidectomy as soon as the mutation is detected or 2 ) to wait for a positive stimulated calcitonin test and then perform a thyroidectomy. Studies from an international consortium lead us to believe that an early prophylactic thyroidectomy is the appropiate course of action
Keywords: FMTC; proto-oncogen RET; codon 611